Clinico Etiological Profile of Upper Gastrointestinal Bleeding in Children from Northernmost India - Latief, Saba; Malik, Ishaq; Nucksheeba, A.; Mushtaq, Sheikh; Muzafar, Jan (British Journal of Healthcare and Medical Research, 2022)
Background: Gastrointestinal bleeding in children has a reported incidence of 6.4%. The study is done to look for the clinico-etiological profile of Upper gastrointestinal (UGI) bleeding in children aged up to 18 years. Methods: This is a prospective, observational study conducted in the Department of Pediatrics, Govind Ballabh Pant Hospital, J&K, Srinagar, India from December 2019 to December 2021. Children below 18 years of age presenting with hematemesis and/or malena were included. History, clinical exam, and laboratory tests were undertaken. Upper GI endoscopy was done within 24 hours of bleeding or after stabilization. Bleeding was divided into variceal and non-variceal, depending on the Upper GI scopy findings. Results: A total of 95 patients were included. 74/95 (77.9%) were in the age group of 06-18 years. Hematemesis was the most common presenting symptom. Bleeding was non-variceal and variceal in 55/95 (57.90%), and 40/95 (42.10%) cases respectively. Bleeding was major and minor in 51/95 (53.5%) and 44/95 (46.45%) respectively. EHPVO was the most common cause of variceal bleeds in 39/40 (97.5%) cases. Major bleed was variceal and non–variceal origin in 34/51(66.7%) and 17/51(33.3%) cases respectively; p-value<0.001. Variceal bleed was more common above 6 years of age (69.2% cases). Anemia was present in 63.2% of patients at the time of presentation. Splenomegaly was clinically evident in 40.6% of cases, 94.7% were due to EHPVO. Conclusion: UGIB is more common in the 06-18 years age group. It is predominantly non-variceal in origin. Most of the major bleeds are due to variceal etiology. EHPVO and gastritis are the most common cause of variceal and non-variceal bleed respectively.